The mayor of Casterbridge - Hardy, Thomas, 1840-1928. (London: Penguin, 1994)
Under the influence of rum, Michael Henchard sells his wife and daughter to a sailor. Years later, the widowed wife returns to find her husband the Mayor of Casterbridge.
Keywords: Fathers and daughters -- -- England; Men -- -- Psychology -- -- England; Psychological fiction; England -- -- Social life and customs -- -- 19th century; Wessex (England); English fiction